Rapid increase in atmospheric iodine levels in the North Atlantic since the mid-20th century - Carlos A. Cuevas; Niccolò Maffezzoli; Juan Pablo Corella; Andrea Spolaor; Paul Vallelonga; Helle A. Kjær; Marius Simonsen; Mai Winstrup; Bo Vinther; Christopher Horvat; Rafael P. Fernandez; Douglas Kinnison; et al. (Nature Communications, 2018)
Despite its chemical importance, the evolution of atmospheric iodine concentrations over time is unknown. Here, the authors show that North Atlantic atmospheric iodine levels have tripled since 1950, and propose ozone pollution and enhanced biological production Arctic sea ice thinning as a primary driver.